Impact of Mangrove Degradation on Fisherman's Catch in Tanjung Pilawang - Bayau, Edom; Ririhena, John Etry; Kasehung, dan Evangelina Ivi Theresa (Agrikan Jurnal Agribisnis Perikanan, 2024)
Tanjung Pilawang is a coastal area located in Gura Village, Tobelo District, North Halmahera Regency, to be precise. This area used to be an area that had mangrove and seagrass ecosystems that were categorized as good, but development activities have caused the mangrove ecosystem to decline. The aim of the research is to see the condition of the mangrove ecosystem and the impact on the catches of fishermen who live in the mangrove ecosystem area. The methodology used in this research is descriptive qualitative based on the results of a literature review. Qualitative descriptive is a research method used to describe a topic, object or problem systematically and factually based on the conditions, nature and relationships between the variables studied. The research results show that mangrove damage has occurred in Tanjung Pilawang. This has a big influence on fishermen's catches. This condition can be proven by the fish resources which currently almost no longer exist in the area around the mangroves. Apart from that, the condition of the resource community is bivalves from the types Isognomon sp and Saccostrea sp, crustaceans from the type S. paramamosain (green mangrove crab), which initially existed around the mangrove ecosystem at the research location, but due to degradation and human activities and residential development caused a decline density of bivalves and they no longer even exist. Meanwhile, gastropod resources of the Nerita sp, Tereblia sp and Littorina spp species experienced a decrease in density